2013
DOI: 10.4103/0973-029x.119742
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of dental caries in children with perinatal HIV infection

Abstract: Aim and Objective:The objective is to assess the prevalence of caries in children with perinatal human immunodeficiency virus (HIV) infection.Materials and Methods:Oral examination was performed on children aged 2-12 years with perinatal HIV infection who stayed at ‘Calvary Chapel home of hope for special children’ to assess decayed, missing, or filled primary teeth/decayed, missing, or filled permanent teeth (dmft/DMFT).Results:Prevalence of tooth decay in primary teeth (dmft) for the age group 2-6 years was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
7
2
Order By: Relevance
“…In the scientific literature, the reported mean dmft ranges between 1.5 and 11.8 (Cerqueira, Portela, & Pomarico, ; dos Santos et al, ; Madigan et al, ; Meless et al, ). Contrary to the findings of the current study, another study found the dmft in children with perinatally acquired HIV was significantly lower and comparable to that of normal children (Sahana, Krishnappa, & Krishnappa, ). A meta‐analysis concluded that even though studies reported a high dmft, there was no significant association between the caries experience and HIV‐infection (Oliveira et al, ).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the scientific literature, the reported mean dmft ranges between 1.5 and 11.8 (Cerqueira, Portela, & Pomarico, ; dos Santos et al, ; Madigan et al, ; Meless et al, ). Contrary to the findings of the current study, another study found the dmft in children with perinatally acquired HIV was significantly lower and comparable to that of normal children (Sahana, Krishnappa, & Krishnappa, ). A meta‐analysis concluded that even though studies reported a high dmft, there was no significant association between the caries experience and HIV‐infection (Oliveira et al, ).…”
Section: Discussioncontrasting
confidence: 99%
“…There was no significant variation between girls (0.89 ± 1.37) and boys (0.83 ± 1.20). Several studies have reported mean DMFT ranging from 0.5 to 4.0 (Cerqueira et al, ; dos Santos et al, ; Madigan et al, ; Meless et al, ; Sahana et al, ). The results of the current study highlighted an overall low caries experience (mean DMFT) in the permanent dentition.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of dental caries in primary dentition was 54%, and in permanent teeth it was 41%. Our study showed a low prevalence of dental caries in primary and permanent teeth in HIV‐positive children, which was in agreement to Sahana et al's study, which concluded that the prevalence of tooth decay in primary teeth (dmft) for the 2 to 6‐year age group was 57.15% and 20% for the 7 to 12‐year age group. For the 7 to 8‐year age group, the prevalence of tooth decay in permanent teeth (DMFT) was 16.60% and 21.42% for the 10 to 12‐year age group; 59.25% of the 27 children examined were caries free (40% were boys and 70.58% were girls).…”
Section: Discussionsupporting
confidence: 92%
“…Although the use of active retroviral therapy (ART) in HIV‐infected children has reduced the prevalence of oral manifestations, there is an increase in the prevalence of dental diseases, mainly due to the chronic influence of some factors involved in the process of HIV infection. Among them are the prolonged use of sugary products, changes in salivary flow, and salivary glands caused by the use of drugs, a diet rich in carbohydrates to protein‐calorie replacement, repeated episodes of hospitalization, poor oral hygiene, immunosuppression by infection of HIV, and a lack of information about the practice of promoting oral health …”
Section: Introductionmentioning
confidence: 99%
“…Many studies report high caries prevalence in HIV-infected children (Masiga and M'Imunya, 2013;Nabbanja et al, 2013;Meless et al, 2014), mainly for primary dentition (Oliveira et al, 2015). Others described low caries prevalence (Sahana et al, 2013). Ponnam et al (2012) observed a high frequency of dental caries in HIV-infected children (33%) but without any difference compared with uninfected children (28%) when matched by age and socioeconomic status.…”
Section: Questionsmentioning
confidence: 99%